Comparative Analysis Of Characteristics, Travel Patterns, And Satisfaction Of Train Users During The 2025 Eid Al-Fitr Transportation At Nganjuk And Madiun Stations - Wahyu Tamtomo Adi; Adib Kurniawan; Septiana Widi Astuti; Andri Pradipta; Ocky Soelistyo Pribadi; Dimas Adi Prawira (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2026)
The characteristics of Eid al-Fitr rail passengers can be used as a reference for providing services that meet the needs of rail transportation users. This study aims to analyze and compare the socioeconomic characteristics, travel patterns, mode choice factors, and satisfaction levels of Eid al-Fitr travelers in 2025 with a case study at Nganjuk Station and Madiun Station, East Java. The research used a comparison of quantitative data taken from a questionnaire survey for a total of 1,324 respondents. The results showed that the majority of travelers at both stations were mainly of the productive age, dominated by students/university students, and workers. There were similarities in travel patterns, reasons for mode choice, and the level of satisfaction among respondents who used Eid al-Fitr train transportation. The very high level of satisfaction at both stations indicates that the quality of service is in accordance with the expectations of transportation users. These findings provide strategic recommendations for PT KAI as the operator and the government as the regulator in improving homecoming services by rail transportation.